Collaboration Platforms for Organizational Integration Uses and Benefits: A Review - Ittipat Chinangkulpiwat; Singha Chaveesuk; Wornchanok Chaiyasoonthorn (My University, 2023)
A collaboration platform is a platform that allows employees to collaborate and coordinate their work together with the functionality of platform, for instance, project management, idea sharing, real-time information and data, virtual meeting, task administration, etc. During the pandemic, organizations everywhere in the world widely adopted collaboration platforms. Since the benefit of this platform and remote working trend, the organization is likely to continue using these platforms. Organizational integration is a crucial factor for the success of the organization. Organizational integration which consists of human integration and task integration seems to benefit from the application of a collaboration platform. This research intended to review the use of collaboration platforms and the benefits of collaboration platforms toward organizational integration, which can guide the application for new adopter to adopt and increase productivity for the organization. The finding illustrates that the application of collaboration platforms benefits organizational integration from both human integration and task integration perspectives. Future research aims on the case study where the combination of the collaboration platform may arise to maximize the benefits of organization in the specific purpose.
Keywords: Technology Adoption and User Behaviour; Digital Marketing and Social Media; Big Data and Business Intelligence